(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
The Norwegian Government Pension Fund Global (GPFG) is the world’s biggest sovereign fund, whose assets under management reached 1 trillion dollars in September 2017. It is a stabilization macroeconomic tool meant to smooth out economic cycles by saving during high oil prices and economic upturn and spending during downturns in order to avoid recessions due to oil price slumps. But it is also a savings fund destined to guarantee the fiscal accounts’ sustainability and the intergenerational allocation of the hydrocarbon wealth with a broad investment horizon. This article focuses on the evolution of the GPFG’s investment profile between 1996 and 2016, from a more conservative approach towards a greater portfolio diversification concerning the set of assets and their geographical origin, although during the last six years it was characterized by a certain conservatism related to risk management and by a conflict of interests between portfolio managers and politicians.